2002
DOI: 10.1074/jbc.m206854200
|View full text |Cite
|
Sign up to set email alerts
|

Malarial Dihydroorotate Dehydrogenase

Abstract: The malarial parasite relies on de novo pyrimidine biosynthesis to maintain its pyrimidine pools, and unlike the human host cell it is unable to scavenge preformed pyrimidines. Dihydroorotate dehydrogenase (DHODH) catalyzes the oxidation of dihydroorotate (DHO) to produce orotate, a key step in pyrimidine biosynthesis. The enzyme is located in the outer membrane of the mitochondria of the malarial parasite. To characterize the biochemical properties of the malarial enzyme, an N-terminally truncated version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 45 publications
3
72
0
Order By: Relevance
“…Assay Methodology-The cloning and expression of recombinant P. falciparum and human DHODH were described previously (15). The standard colorimetric DHODH continuous assay that monitors 2,6-dichloroindophenol (DCIP) reduction was adapted to an end-point assay in 384-well plates for compatibility with the high-throughput screening format.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assay Methodology-The cloning and expression of recombinant P. falciparum and human DHODH were described previously (15). The standard colorimetric DHODH continuous assay that monitors 2,6-dichloroindophenol (DCIP) reduction was adapted to an end-point assay in 384-well plates for compatibility with the high-throughput screening format.…”
Section: Methodsmentioning
confidence: 99%
“…Thirdly, species-selective pyrazole-based inhibitors of Hylicobacter pylori and of Escherichia coli DHODH have been reported that were identified by highthroughput screening of chemical libraries (13,14). Finally, we previously demonstrated that P. falciparum DHODH is poorly inhibited by the potent human DHODH inhibitors redoxal, dichloroallyl lawsone, and A77-1726 analogs (15). Thus, these studies suggest it should be feasible to exploit active-site differences to identify inhibitors that exhibit a high degree of selectivity toward malarial DHODH.…”
mentioning
confidence: 99%
“…Fractions containing PfDHODH were pooled and concentrated to 20 mg/ml. The construction and purification of the H185A, F188A, F227A, and R265A mutant PfDHODH enzymes were described previously (12,19).…”
Section: Gene Cloning Of Pfdhodh-n-terminally Truncatedmentioning
confidence: 99%
“…Enzyme Kinetic Analysis-Steady-state kinetic analysis was performed as described previously (12,19). To determine the k cat and K m of PfDHODH ⌬384 -413 in comparison with the wildtype enzyme the direct assay that follows the oxidation of DHO at 296 nM (⑀ ϭ 4.3 mM Ϫ1 cm Ϫ1 ) was used (Supplemental Table S1).…”
Section: Gene Cloning Of Pfdhodh-n-terminally Truncatedmentioning
confidence: 99%
See 1 more Smart Citation